Lessons from Two Decades of Research about Successful School Leadership in England: A Humanistic Approach - Monica Mincu; Alyson Colman; Christopher Day; Qing Gu (MDPI AG, 2024)
This paper reviews the research on successful school principalship carried out in England over the last 20 years. Drawing on evidence synthesized from the International Successful School Principalship Project (ISSPP) and related English school leadership research conducted by ISSPP scholars, this review aims to answer a conceptual research question: How do the principalship's moral purposes and contextual understanding shape the time-sensitive, informed adoption of combinations and accumulations of strategies that lead to sustained school success? This paper identifies five research insights derived from case studies in England and elaborates on the complex, values-led layered web of interactions between the school principal and key stakeholders within and outside the school in the context of frequent social changes and policy interventions in England. Whilst the pace has been greater and more intense than in many other countries, the direction has been, and remains, similar. The body of scholarship here reviewed engages with national policies as filtered and then enacted by successful principals. While 'effective' principals lead to students' success as measured by performance on national tests and examinations, our focus is upon an empirically founded definition of 'successful' school leadership that is located in complexity theory and encompasses the enactment of the core purposes of education that include but go beyond the functional. In doing so, it avoids 'what to do' formulae and the limitations of certain theoretical 'leadership' models, finding that successful school leaders' work embodies a broader humanistic view of student learning and achievement, which implies the preordinance of the personal over the functional. Taken together, these research insights contribute to the ISSPP's continued effort to refine and advance the knowledge base of successful school leadership within and across different countries.